2017
DOI: 10.12911/22998993/76901
|View full text |Cite
|
Sign up to set email alerts
|

The Problems in Achieving Sustainable Development in the Tannery Industry in Regard to Sewage Sludge Management

Abstract: The paper discusses the issue of tannery sewage sludge management as one of the barriers in reaching sustainable development in the tanning industry. The Authors present the main characteristics, and its origins, of tannery sludge limiting the possibilities of their treatment and review the proposed solutions found in literature. The paper focuses on identifying the strong and weak points of the most commonly used methods used for sewage sludge treatment as well as presents some novel approaches which remain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 43 publications
0
5
0
1
Order By: Relevance
“…On the other hand, Christopher et al (2016) reported an average concentration of chromium in wastewater of only 500 mgCr/dm 3 . The significant concentrations of chromium in wastewater and the high use of these compounds by up to 90% of all tanning facilities boil down to the fact that the tanning industry is considered one of the most polluting in the world and responsible for about 40% of global chromium pollution (Bień et al, 2017;Celary & Sobik-Szołtysek, 2014;Chmielowski, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, Christopher et al (2016) reported an average concentration of chromium in wastewater of only 500 mgCr/dm 3 . The significant concentrations of chromium in wastewater and the high use of these compounds by up to 90% of all tanning facilities boil down to the fact that the tanning industry is considered one of the most polluting in the world and responsible for about 40% of global chromium pollution (Bień et al, 2017;Celary & Sobik-Szołtysek, 2014;Chmielowski, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…With undisturbed course of the process, the ratio of alkalinity to VFA should not exceed 0.3 [20] whereas inhibition of the development of methanogens in the reaction chamber occurs when its value exceeds 0.8 [21]. In the first days of the experiment, the VFA/alkalinity ratio was very high: 0.7 (2 nd day) and 0.36 (6 th day).…”
Section: Methodsmentioning
confidence: 99%
“…Kavouras et al, (2015), comentam que as características dos agentes poluidores, em quantidade e qualidade, do curtume dependerão de diversos fatores, como tecnologias empregadas no processo fabril, perfil de produto produzido, opções de tratamento de efluentes empregadas e outras mais. Bień et al, (2017), cita ainda que diversas opções de tratamento destes agentes poluidores estão sendo combinadas para prover maior eficiência na redução da carga poluidora, e consequentemente os impactos no ambiente.…”
Section: Da Indústria Do Courounclassified